The relevance of integrated reporting in future standard setting of the International Sustainability Standards Board - van Wyk, Milan; Els, Gideon (Frontiers in Sustainability, 2023)
Sustainability reporting has become increasingly important to stakeholders and therefore there is a growing need for a global set of standards on sustainability reporting. The International Sustainability Standards Board (ISSB) has recently published new sustainability standards under the International Financial Reporting Standards (IFRS) Foundation. The consolidation of integrated reporting into the IFRS Foundation creates a problem of whether there is still a need for principles in the future of sustainability reporting and how these principles will be applied in standard setting of the ISSB in the future. This paper provides insights into the similarities and differences between the Framework and the ISSB’s draft IFRS S1 standard and clarifies the role that could play in the future of sustainability reporting within the context of the newly issued IFRS S1 standard. The paper uses thematic content analysis on the two frameworks and comment letters submitted to the ISSB as part of the standard-setting process to understand the relevance of integrated reporting in sustainability reporting and to identify important principles contained within that can contribute to the ISSB standard setting process in the future. The paper identified that there is a largely positive sentiment towards in developing sustainability standards within the IFRS Foundation. The paper also identified important aspects where can play a significant role in standard development such as the connectivity of information, integrated thinking and the six capitals that can assist organizations in understanding the significant sustainability related risks and opportunities. The research points out pertinent sustainability principles that could be useful for the ISSB in future standard setting. Furthermore, the research adds to the existing literature on and can act as an impetus for further research on the use of principles in the standards setting processes of the ISSB.